CLINICAL AND LABORATORY FEATURES OF THYMOMEGALY IN YOUNG CHILDREN - Umarova T. A.; Kudratova Z. E.; Fayziyeva B. (Web of Journals Publishing, 2025)
Thymomegaly - hyperplasia of the thymus and its hypofunction, accompanying a number of diseases of childhood. Minor thymomegaly is asymptomatic; pronounced thymus enlargement may manifest with vital organ compression syndrome, lymphoproliferation syndrome, immune and endocrine-exchange disorders [6,7,8,9].
Keywords: Thymomegaly, thymus gland, immune system, chest radiography, endocrine disorders.